The beneficial effects of meditation: contribution of the anterior cingulate and locus coeruleus - Craigmyle, Nancy A. (Frontiers in Psychology, 2013)
Abstract During fMRI studies of meditation the cortical salience detecting and executive networks become active during “awareness of mind wandering”, “shifting” and “sustained attention”. The anterior cingulate (AC) is activated during “awareness of mind wandering”. The AC modulates both the peripheral sympathetic nervous system (SNS) and the central locus coeruleus (LC) norepinephrine systems, which form the principal neuromodulatory system, regulating in multiple ways both neuronal and non-neuronal cells to maximize adaptation in changing environments. The LC is the primary source of central norepinephrine (C-NE) and nearly the exclusive source of cortical norepinephrine. Normally activated by novel or salient stimuli, the AC initially inhibits the SNS reflexively, lowering peripheral norepinephrine (P-NE) and activates the LC, increasing C-NE. Moderate levels of C-NE enhance working memory through alpha 2 adrenergic receptors, while higher levels of C-NE, acting on alpha 1 and beta receptors, enhance other executive network functions such as the stopping of ongoing behavior, attentional set shifting and sustained attention. The actions of the AC on both the central and peripheral noradrenergic systems are implicated in the beneficial effects of meditation. This paper will explore some of the known functions and interrelationships of the AC, SNS and LC with respect to their possible relevance to meditation.